HUBUNGAN EXPLOSIVE POWER OTOT LENGAN DAN BAHU DAN KOORDINASI MATA TANGAN DENGAN KEMAMPUAN SHOOTING TIM BASKET PUTRA SMA NEGERI 1 PEKANBARU - Perdana, Bryan Danes; Juita, Ardiah; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research are when got a shoot in to the ring, the ball are not in and in another time the ball are not touching the ring (airball), so that the man basketball team of senior high school 1 pekanbaru are poinless. And the problems come from the player are not having a technique well, and based on observation, researcher found that player does mistake when they are doing a shoot. This mistake considered happen because of there is no hands and shoulder explosive muscular power to push the ball in to the ring and a good eye-hand coordination when doing a shoot. The goal of this research is to know about correlation of hands and shoulder explosive muscular power and eye-hand coordination with shooting ability in basketball game on Man Basketball Team of Senior High Shool 1 Pekanbaru.This research contains of three variables which are; hands and shoulder explosive muscular power (X1), eye-hand coordination (X2), and shooting ability (Y). The sample took the whole sample (total sampling) of Senior High School 1 Pekanbaru man basketball team that contains of 12 players. The data collected by using vertical power jump instrument, throw and catch tennis ball, and shooting test. Data processing used correlation method which using normality test, correlation of product-moment test, The normality test of variable X1, L0max (0,20) < Ltable (0,242), normality test of variable X2, L0max (0,13) < Ltable (0,242), and normality test of variable Y, L0max (0,20) < Ltable (0,242). On significant stage of 0,05 if L0maks < Ltabel means the population distributed normally. The product-moment test of X1Y Rhitung (0,66) < Rtabel (0,602), the product-moment test of X2Y Rhitung (0,87) < Rtabel (0,602), and product-moment test of X1X2Y Rhitung (0,91) < Rtabel (0,602).so that the Hyphotesis o are not allowed and the Hyphotesis a are accept. Based of the research there are a correlation of hands and shoulder explosive muscular power (X1) and eye hand coordination (X2) with shooting ability (Y) on man basketball team of Senior High School 1 Pekanbaru.Keywords : Explosive muscular power, Eye hand coordination, Shooting ability